The generic mitigating circumstances of the article 46 of the Peruvian Criminal Cod - Prado Saldarriaga, Víctor Roberto (2015)
Due to the enactment of the 30076 Act, which modified the Peruvian Criminal Code, the author of this article analyses and explains the changes made in the article 46. With that purpose, he develops the meaning of the “circumstances”in criminal matters, and the reason for being of mitigation and aggravation.Furthermore, the author analyses in detail the eight generic mitigating circumstances that the modified article introduces (the age of the imputed, the voluntary reparation after committing the illicit act, the absence of a criminal record, among others), explaining them and realizing a comparison between what other criminal codes around the world, our old code and the new article 46 estipulate.